GOLD IN THE EARTH'S CRUST AND UPPER MANTLE OF TAJIKISTAN - Gavrilenko B.V.; Minaev V.E. (My University, 2003)
Gold distribution in sedimentary, volcanic, and intrusive rocks, and mantle xenoliths of the southern Tien Shan and Pamirs is characterized using 2900 analyses. The metal concentration is somewhat higher in the intrusive (3.5 ppb) than volcanic-sedimentary (2.4 ppb) rocks and increases from 1.7 ppb in Archean to 5.0 ppb in Cenozoic volcanic-sedimentary formations. The highest gold concentrations of sedimentary and volcanic rocks were found in pelites and basalts. Gold concentration of basaltic rocks decreases with an increase in their alkalinity. Granite porphyries and aplites of a dike complex have the highest gold concentrations (7.0 ppb) among the intrusive rocks. Gold concentration in the Earth's crust of Tajikistan slightly increases from 2.4 ppb in the sedimentary layer to 3.4 ppb in the granite-metamorphic layer and 3.5 ppb in the granulite-basite layer. For the Pamirs and Tien Shan, gold concentration is 3.3-3.5 ppb in the crust and 3.5-3.7 ppb in the upper mantle. These values correspond to the gold concentrations in the rocks of platforms and folded belts in the other regions.